A comparative analysis of place branding in Michigan and Ontario. Issue 1 (2nd January 2016) - Sadler, Richard; Cleave, Evan; Arku, Godwin; Gilliland, Jason
Abstract : Place branding has increasingly been adopted as a municipal initiative to change the trajectory of local economic development. Specifically, local municipalities and communities have used place branding not only as a response to the influence of globalization and neo-liberalism, but also economic challenges and restructuring. Like any other initiative, the ultimate goal is to enhance the economic and social well-being of local jurisdictions. Although a popular strategy, it is not clear if and how locally specific factors mediate the process. By comparing two cross-border geographical areas, this study attempts to identify how regional variability in the manifestation of political-economic forces, as well as geographical influences, affects the use of place branding at local scales. Every municipality in Michigan ( n  = 1774) and Ontario ( n  = 414) was systematically examined for the presence and message of local place brands as presented through logos and slogans. The comparative analysis demonstrated that Ontario's municipalities utilized place branding to a greater extent, and that the dominant messages differ by region. Further, this analysis shows that – beyond political differences – geographical context appears to have an effect on both local place branding usage and message.